Hydrogen bond directed honeycomb-like porous network structure of tris (bipyridyl-glycoluril)cobalt(III) chloride - Kawade, Vitthal A.; Kumbhar, Avinash S.; Erxleben, Andrea; Pachfule, Pradip; Banerjee, Rahul (Crystengcomm, 2011)
The [Co(bpg)3]Cl-3 complex (1), where bpg = 4b, 5, 7, 7a-tetrahydro4b,7a-epiminomethan-oimino-6H-imidazo [4,5-f][1,10]-phenanthroline-6,13-dione has been synthesized and characterized by various spectroscopic techniques and single crystal X-ray diffraction. The combination of bipyridyl-glycoluril (bpg) ligands and cobalt ion self-organise to form a honeycomb-like porous network structure resulting in the formation of zeolite like channels which adsorb gases, is described.